(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Thestudy explores the evolution of Human Talent Management (HTM) from an operational approach to a central strategy in contemporary organizations. Previous studies highlight that human talent includes not only technical skills, but also soft skills that are crucial for organizational success. The methodis quantitative and correlational, using structured questionnaires to collect data from 50 medium and large companies. The sample was selected by non-probabilistic convenience sampling. Statistical analysis was performed with SPSS software, evaluating the relationship between HTM and organizational performance variables, such as productivity, sales growth, and customer satisfaction. A high correlation was found between the effective management of human talent and sales growth (0.998), as well as with productivity (0.964). CSR practices are strongly linked to employee satisfaction and a positive impact on the community.This demonstrates that strategic management of human talentenhances organizational performance and positions companies better to compete in a globalized and changing environment.